Experimental characterization of chemical mineral composition and morphology of titanium in carbonized slag particles - Jianxin Wang; Dong Yue; Liangying Wen; Liwen Hu; Xueming Lv (Journal of Materials Research and Technology)
The form of titanium in the carbonized slag particles has a significant influence on the efficiency in the selective fluidized chlorination process for extracting titanium. The carbonized slag particles is made from water quenching and wind grinding after the reduction of titanium-bearing blast-furnace slag in high-temperature electric carbide furnace. Based on the analysis of chemical mineral composition and particles size, it is concluded that the carbonized slag is a low-grade titanium raw material with high impurity content, uneven particle size and wide distribution range, and the only crystal phase obtained by detection is TiCxOy. According to the analysis of the occurrence state of titanium element using SEM-EDS and mineral liberation analyzer (MLA), the results indicate that almost all titanium in the titanium-bearing blast-furnace slag exists in the CaTiO3 phase, which is transformed into TiCxOy phase during the process of carbonization reduction to make the carbonized slag. The TiCxOy phase is diffusely distributed within the carbonized slag particles. The larger the particle size of the carbonized slag, the more concentrated the TiCxOy phase is within the particle and vice versa. The residual iron beads within the carbonized slag particles could increase the degree of carbonization reduction of the surrounding titanium oxides to form TiCx.